Regulation Prohibiting the Use of Plastic Bags in Sales Transactions in Makassar City A Constitutional Perspective : (Makassar Mayor Regulation No. 21 of 2023) - Muh. Iqbal Pratama; Sabri Samin; Dea Larissa (Yayasan pendidikan dzurriyatul Quran, 2026)
The increase in plastic waste in Makassar City has caused significant environmental problems, including overcapacity of landfills and environmental degradation. This condition has prompted the local government to implement a policy banning the use of plastic bags, with the aim of protecting the environment and community welfare. This study aims to analyze the causes, impacts, and utilization of plastic bags in supporting environmental cleanliness in Makassar City from the perspective of Siyasah Dusturiyah. This study uses qualitative methodology, supported by a theological (sharia) and judicial normative framework. Data sources include the Makassar City Government, the Environmental Agency, and the community. Data were collected through various methods, including observation, interviews, documentation, and literature review. The data was then analyzed through a series of stages, including classification, identification, editing, reduction, and verification. The findings show that the ban on plastic bags was triggered by the increasing volume of plastic waste, limited landfill capacity, and environmental degradation. This policy has proven to have a positive impact, including a reduction in plastic waste and increased environmental protection. However, the implementation process posed a number of challenges, especially for traditional market traders and low-income communities. In addition, the continued use of plastic bags, albeit in limited quantities, still provides tangible benefits in terms of maintaining cleanliness, especially in the context of household waste management. From a Siyasah Dusturiyah perspective, this policy is in line with the principles of public interest, justice, and environmental sustainability. The implications of the study emphasize the importance of a balanced policy implementation approach that considers both environmental protection and community needs.